Validation on carbon dioxide hydrate formation through analysis on the solubility of CO2 in water using Henry’s law and the experimental pressure-time curve - Hassan M.H.A.; Snape C.E.; Stevens L. (Malaysian Society of Analytical Sciences, 2024)
Indexed by Scopus